2011
DOI: 10.4283/jmag.2011.16.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Embrittlement in Isochronal Aged Fe-Cr Alloys by Magnetic Hysteresis Loop Technique

Abstract: Fe-Cr alloys with different Cr contents were prepared by an arc melting technique. The alloys were isochronally aged in the range from 400 o C to 900 o C with 50 o C steps with a holding time of 100 hours. The ageing produced embrittlement in the alloys due to either the formation of a Cr-rich α' phase or a σ phase at high temperatures. Magnetic Hysteresis Loop (MHL) and Micro-Vickers hardness were measured at each step to correlate the magnetic and mechanical properties. Coercivity and hardness of the alloys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In our earlier work correlations between the change in mechanical and magnetic properties were found with the formation and growth of Cr rich a 0 phase in Fe-Cr alloys [9,10]. At large volume fraction of s phase magnetic properties changes significantly [11], however at small volume fraction of s phase the behavior of magnetic properties has not been investigated.…”
Section: Introductionmentioning
confidence: 94%
“…In our earlier work correlations between the change in mechanical and magnetic properties were found with the formation and growth of Cr rich a 0 phase in Fe-Cr alloys [9,10]. At large volume fraction of s phase magnetic properties changes significantly [11], however at small volume fraction of s phase the behavior of magnetic properties has not been investigated.…”
Section: Introductionmentioning
confidence: 94%
“…It has been reported that phase separation is enhanced by irradiation when the irradiation flux is relatively low and the cascade mixing effect is small, even in the low-temperature range where separation does not occur by thermal aging [11,12]. In the studies investigating the magnetic properties of ion-irradiated Fe- (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)%Cr films, an increase in coercivity and magnetization was reported [13][14][15]. The irradiation-enhanced phase separation is considered the reason behind these phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, when examining iron-chromium alloys where chromium is introduced to pure iron, it is important to consider not only the formation of dislocation loops and void clusters caused by irradiation but also the changes in the arrangement of chromium atoms. By thermal aging, the Fe-Cr solid solution is known to undergo phase separation into Fe-rich and Cr-rich phases at high temperatures [8], which affects the magnetization process of the alloys [9,10]. It has been reported that phase separation is enhanced by irradiation when the irradiation flux is relatively low and the cascade mixing effect is small, even in the low-temperature range where separation does not occur by thermal aging [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, magnetic-based testing approaches can be used for testing duplex stainless steels, since these tests are sensitive to the presence and amount of the ferromagnetic ferrite phase. Mohapatra et al [19,20] showed that the remanence measurement of the magnetic hysteresis loop is able to follow the formation of the σ phase even when presented in low volume fractions. Structure-sensitive magnetic properties like coercivity and remanence are affected by microstructural modifications.…”
Section: Introductionmentioning
confidence: 99%